2000
DOI: 10.1094/cchem.2000.77.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Grain Hardness, Pentosan Fractions, and End‐Use Quality of Wheat

Abstract: Cereal Chem. 77(2):241-247Grain texture (hardness) in wheat (Triticum aestivum L.) is a major determinant of end-usage. Variation in grain texture can be conceptually assigned to the two major hardness classes that result from the action of one major gene (Hardness) or to as-yet undetermined factors contributing to residual variation within hardness classes. Identifying the physicochemical basis of both sources of texture variation could provide a means of better controlling or manipulating this quality trait.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 11 publications
(15 reference statements)
8
76
1
3
Order By: Relevance
“…Cookie diameter was influenced by hardness index, milling performances and physico-chemical properties, and especially by the particle size of flour, damaged starch content and SDS-sedimentation volume. Pina-D1a/Pinb-D1a had larger cookie diameter than other genotypes, which is in agreement with the report of Bettge and Morris (2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cookie diameter was influenced by hardness index, milling performances and physico-chemical properties, and especially by the particle size of flour, damaged starch content and SDS-sedimentation volume. Pina-D1a/Pinb-D1a had larger cookie diameter than other genotypes, which is in agreement with the report of Bettge and Morris (2000).…”
Section: Discussionsupporting
confidence: 92%
“…Hardness index was significantly correlated with flour yield and the proportion of break flour in Korean wheats with all puroindoline genotypes, but no significant relationships were found in Korean hard wheats. However, hardness index was negatively correlated with flour yield in hard wheats (Ohm et al 1998, Martin et al 2001 and Chinese winter wheats (Zhang et al 2005) and also negatively correlated with break flour yield in US wheats with various puroindoline genotypes (Bettge and Morris 2000).…”
Section: Discussionmentioning
confidence: 94%
“…The presence of DFAs in bran could enhance cross linking with arabinoxylan chains (Gallardo et al, 2006) hence affecting grain mechanical properties (Renger & Steinhart, 2000). Arabinoxylans were shown to have a greater effect in modifying grain hardness in soft wheat than in hard wheat (Bettge & Morris 2000). High levels of polymer similar to water soluble arabinoxylans characterized the peripheral endosperm of soft wheat cultivars (Barron, Parker, Mills, Rouau & Wilson 2005).…”
Section: Identification and Quantification Of Diferulic Acidsmentioning
confidence: 99%
“…A negative correlation of -0.45 between these traits was also observed in hard wheat (Gross et al, 2004) and others have reported a negative correlation between these traits in soft wheat (Smith et al, 2011;Cabrera et al, 2015;Hoffstetter et al, 2016). Genetic studies of kernel hardness in bread wheat indicated that phenotypic expression of kernel hardness was tightly linked with FP (Galande et al, 2001), but additional related traits such as arabinoxylan content also played an important role in kernel hardness (Bettge & Morris, 2000).…”
Section: Wheat Quality Laboratory (Swql) Of the United States Departmmentioning
confidence: 78%